Phase locked loop system with combined control of tunable oscillator - Печенин, В.В.; Щербина, К.А.; Мсаллам, Е.П.; Вонсович, М.А. (Radiotekhnika, 2016)
The presented study provides the research results related to the further improvement of the combined phase locked loop control systems with the controlled element – voltage controlled oscillator. The carried out research is aimed at development of a tracking system that improves the basic performance indices in tracking meters used in radar location systems, radio navigation systems, communication and other wireless devices and systems of receiving and processing signals with the regular slow-varying frequency component, referred as the Doppler signals, generated during normal-mode interference.